Effectiveness of simple approaches in mitigating residual deformations in buildings. - Pettinga, Didier (Earthquake engineering & structural dynamics.)
Developments in performance-based seismic design and assessment approaches have emphasized the importance of considering residual deformations. Recent investigations have also led to a proposed direct displacement-based design (DDBD) approach which includes an explicit consideration of the expected residual deformations as an integral part of the design process. Having estimated the expected residual deformations in a structure, engineers are faced with the problem of reducing them to meet the targeted performance levels under pre-defined seismic hazard levels. Previous studies have identified the post-yield stiffness as a primary factor influencing the magnitude of residual deformations in single degree of freedom and multiple degree of freedom structures. In this paper, a series of simple approaches to increase the post-yield stiffness of traditional framed and braced systems for the purpose of reducing residual deformations are investigated. These methods do not utilize recentring post-tensioned technology. This contribution addresses the feasibility of altering the lateral post-yield stiffness of structural systems by: (i) using different reinforcement materials with beneficial features in their stress?strain behaviour; (ii) re-designing the section geometry and properties of primary seismic-resisting elements; and (iii) introducing a secondary elastic frame to act in parallel with the primary system. The efficiency of each of these techniques is investigated through monotonic and cyclic moment-curvature and non-linear time-history analyses. Of these approaches the design and introduction of an elastic secondary system was found to be most effective and consistent in reducing residual deformations. A simplified design approach for achieving the desired increase of a system's post-yield stiffness is also presented.